1982
DOI: 10.1021/bi00269a052
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the complex of the Rhizopus chinensis carboxyl proteinase and pepstatin at 2.5 .ANG. resolution

Abstract: An X-ray diffraction analysis has been carried out at 2.5-A resolution of the three-dimensional structure of the Rhizopus chinensis carboxyl proteinase complexed with pepstatin. The resulting model of the complex supports the hypothesis [Marciniszyn, J., Hartsuck, J.A., & Tang, J. (1976) J. Biol. Chem. 251, 7088-7094] that statine (3-hydroxy-4-amino-6-methylheptanoic acid) approaches an analogue of the transition state for catalysis. The way in which pepstatin binds to the enzyme can be extended to provide a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(101 citation statements)
references
References 32 publications
4
96
0
1
Order By: Relevance
“…Firstly, the replacement of the water or hydroxonium ion capable of hydrogen bonding with the negatively charged aspartates by the carbonyl oxygen of the substrate peptide [24] would be unfavourable. On the other hand, replacement by the hydroxyl of a pepstatin inhibitor which could form a hydrogen bond analogous to that of water would cause no difficulty.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the replacement of the water or hydroxonium ion capable of hydrogen bonding with the negatively charged aspartates by the carbonyl oxygen of the substrate peptide [24] would be unfavourable. On the other hand, replacement by the hydroxyl of a pepstatin inhibitor which could form a hydrogen bond analogous to that of water would cause no difficulty.…”
Section: Resultsmentioning
confidence: 99%
“…The assignments for Sd-Si were refined and largely confirmed by direct X-ray studies of inhibitors bound to penicillopepsin [28] and to rhizopuspepsin [27]. There are no direct studies which unequivocally define S{-S;, but the original assignments have been improved by more precise modelling using the refined coordinates of endothiapepsin.…”
Section: Human Renin Human Pepsinmentioning
confidence: 91%
“…The residues P4-Pi were placed by analogy with the inhibitors bound to rhizopuspepsin [27] and penicillopepsin [28]. This brought the scissile bond into close juxtaposition with a water molecule bound to the two active site aspartates [29].…”
Section: Methodsmentioning
confidence: 99%
“…Recent NMR studies, indicating that water; rather than a carboxyl group, is the nucleophile, have provided additional evidence against covalent intermediate formation during catalysis by the aspartic proteases [14]. X-ray crystallographic studies have also suggested that the formation of--a covalent acyl-or amino-enzyme is not feasible because of steric hindrance [8,15].…”
mentioning
confidence: 99%